Changes in hematological biomarkers of Nellore cows at different reproductive stages - Wagner Dias Coelho de Oliveira; Tairon Pannunzio Dias e Silva; Marcos Jácome de Araújo; Ricardo Loiola Edvan; Ronaldo Lopes Oliveira; Leílson Rocha Bezerra (Acta Scientiarum. Animal Sciences, 2019)
This study was conducted to evaluate changes in hematological biomarkers of Nellore cows at different reproductive stages. Fifteen multiparous cows with 4 ± 1 years of age and live weight of 400 ± 50 kg were used at different stages (non-pregnant, in the initial, middle and late pregnancy, at birth, one day postpartum, 30 and 60 days postpartum). Blood collections were performed every 30 days and assayed for the following hematological biomarkers: hemogram (red blood cells, globular volume, hemoglobin, mean corpuscular volume (MCV) and mean corpuscular hemoglobin concentration (MCHC)) and leukogram (total and differential counts). The erythrogram was influenced (p < 0.001) by the reproductive stages, with variation in the results obtained for the total red cell count, hemoglobin content, globular volume, MCV, MCHC and total plasma proteins. The reproductive stages influenced the leukocyte profile with variation in the total leukocyte count and in the absolute values of neutrophils, eosinophils, lymphocytes and monocytes. Hematological biomarkers of Nellore cows showed significant changes due to the physiological adjustments required in response to the metabolic requirements imposed in the final stage of pregnancy and in the beginning of lactation, ensuring the nutritional contribution in energy and oxygen transported through the blood.